2015
DOI: 10.1186/s12944-015-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of serum lipid contents in pre and post IFN-alpha treated acute hepatitis C patients

Abstract: BackgroundTo study the effect of Interferon (INF) alpha-2b therapy on the serum lipids and fatty acid (FA) level in pre and post treated hepatitis C (HCV) patients.MethodsFifty samples were collected from pre and post treated patients along with age and gender matched controls. After separating serum, lipid contents were analyzed by microlab and gas chromatography.ResultsThe hepatitis C infection results in hypolipidemia with reduced level of triglyceride (113 mg/dl), high density lipoprotein (37.1 mg/dl), low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The palmitic and stearic acid in free form is significantly higher in hepatitis B patients. The FFA contain lipotoxic properties reported in the literature [ 36 ]. The saturated FFA’s, palmitic acid and stearic acid are more cytotoxic than monounsaturated FFAs.…”
Section: Discussionmentioning
confidence: 99%
“…The palmitic and stearic acid in free form is significantly higher in hepatitis B patients. The FFA contain lipotoxic properties reported in the literature [ 36 ]. The saturated FFA’s, palmitic acid and stearic acid are more cytotoxic than monounsaturated FFAs.…”
Section: Discussionmentioning
confidence: 99%
“…The palmitic, palmitoleic, stearic and myristoleic acids are elevated in free form in HBV-cirrhosis patients. Most of the literature has focused on the lipotoxic properties of FFAs [ 49 , 50 ]. Malhi et al [ 51 ] indicated that FFAs can have diverse cellular and metabolic effects particularly stearic acid is more cytotoxic than palmitic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The HCV lipo‐viral particles contain increased levels of apoC‐III that may inhibit the activity of lipoprotein lipase, disturbing the intravascular catabolism of TG‐rich lipoproteins . Moreover, the profiles of serum lipids, such as TG, Chol, LDL‐C and HDL‐C, were reduced in patients with acute and chronic HCV infection . An increasing body of evidence demonstrated that HCV may modulate lipid metabolism and promote the synthesis of saturated fatty acids by controlling the enzymes in the lipid synthesis pathway .…”
Section: Chronic Hepatitis Viral Infection and Lipid Profilesmentioning
confidence: 99%